Midiendo la pobreza a partir de la percepción de los propios individuos : Un cálculo para Colombia y el Valle del Cauca de la línea de pobreza subjetiva - Luis Fernando Aguado Quintero; Ana Maria Osorio Mejía; Jaime Rodrigo Ahumada Castro; Gloria Isabel Riascos Correa (Colegio de Economistas de A Coru\~na, 2007)
– In this article a line of subjective poverty is estimated by means of the answers of the Colombian and Valle del Cauce people to the question of suffieciency of income of the Living Conditions Survey (ECV2003). The results show that a Colombian home is considered poor when its income in colombian pesos is lower than 1.142.097, while in Valle del Cauca, this figure is 872.545. The difference between the value of the subjective line for the national average and for Valle del Cauca suggests that multiple issues influence the perception of poverty, which we hope to study in another document, and the empirical literature associates them with the regional economic characteristics and the different supplies of human and social capital. The subjective measurements of poverty complement the objective measurements (generally based on income) and jointly constitute the bases for a better comprehension of poverty and the design of effiective politics to overcome it.
Keywords: 330; Armut; Messung; Lebensqualität; Kolumbien; Valle del Cauca